2006 IEEE Aerospace Conference
DOI: 10.1109/aero.2006.1656041
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Time Critical Decision Making Models and Human Cognitive Processes

Abstract: Abstract-From a general cognitive perspective, decision making is the process of selecting a choice or course of action from a set of alternatives. A large number of time critical decision making models have been developed over the course of several decades. This paper reviews both the underlying cognitive processes and several decision making models. In the first section, we briefly describe the primary underlying cognitive processes and issues that are common to most, if not all, decision making models, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 21 publications
1
24
0
2
Order By: Relevance
“…It can be shown that such irrational decision making behaviors are actually rational when considering the broader decision making process model presented in this paper. Several studies have shown the need for developing decision making models based on the human cognitive processes; for example see Azuma et al (2006) and Endsley et al (2007). The model developed in this paper also considers the human cognitive processes.…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that such irrational decision making behaviors are actually rational when considering the broader decision making process model presented in this paper. Several studies have shown the need for developing decision making models based on the human cognitive processes; for example see Azuma et al (2006) and Endsley et al (2007). The model developed in this paper also considers the human cognitive processes.…”
Section: Introductionmentioning
confidence: 99%
“…The model also suggests that humans make quick decisions in such situations by matching the current situation with past experiences and selecting solutions to similar situations. Similar ideas were also advocated in [10,15,16].…”
Section: Related Workmentioning
confidence: 56%
“…Pada proses pemecahan masalah, individu menggunakan pengetahuan dan penalaran untuk memutuskan apa yang harus dilakukan, menyimpulkan cara terbaik dalam mencapai tujuan dan menentukan konsekuensi dari keyakinan tindakan yang diambil [7] [13]. Dalam praktiknya, salah satu komponen penting pendukung proses pemecahan masalah adalah dengan mengingat pengalaman sebelumnya pada situasi yang sama [14] [15].…”
Section: Pendahuluanunclassified